2008
DOI: 10.1073/pnas.0710473105
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced metallization of silane

Abstract: There is a great interest in electronic transitions in hydrogen-rich materials under extreme conditions. It has been recently suggested that the group IVa hydrides such as methane (CH 4), silane (SiH4), and germane (GeH 4) become metallic at far lower pressures than pure hydrogen at equivalent densities because the hydrogen is chemically compressed in group IVa hydride compounds. Here we report measurements of Raman and infrared spectra of silane under pressure. We find that SiH 4 undergoes three phase transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
172
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(183 citation statements)
references
References 28 publications
9
172
0
Order By: Relevance
“…10,11 Only one solid phase has been reported in the pressure range between 10 and 25 GPa with a monoclinic structure at room temperature. 12 At pressure above 60 GPa, Chen et al 13 found the pressure-induced metallization for silane by analyzing the infrared reflectivity data at room temperature.…”
mentioning
confidence: 99%
“…10,11 Only one solid phase has been reported in the pressure range between 10 and 25 GPa with a monoclinic structure at room temperature. 12 At pressure above 60 GPa, Chen et al 13 found the pressure-induced metallization for silane by analyzing the infrared reflectivity data at room temperature.…”
mentioning
confidence: 99%
“…Experiments conducted in diamond anvil cells show that SiH 4 liquefies at 1.7 GPa and then solidifies at 4 GPa forming phase III † as evidenced by the Raman spectroscopy [4]. Upon further compression silane enters phase IV (at 6.5 GPa) and then V (at 10 GPa) [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…try) [5], is stable up to 26.5 GPa [4,5]. Above this pressure SiH 4 has been reported to undergo a gradual phase transition with phase V coexisting with a new phase VI over a broad range of pressures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations